Labor economics and labor relations - Reynolds, Lloyd George (Englewood Cliffs, N.J., Prentice-Hall, 1949)
Analyzes the field of labour economics and labour relations, covering labour market economics, wage determination, union organization, collective bargaining and the economic effects of unionization. Emphasis is placed on policy applications of labour economics and changes in industrial relations.
Includes bibliographies.
rpm 01/03/2018
Loans
Keywords: Labor economics; Industrial relations